Benzylated and prenylated flavonoids from the root barks of Cudrania tricuspidata with pancreatic lipase inhibitory activity. Issue 17 (1st September 2015) - Jo, Yang Hee; Kim, Seon Beom; Liu, Qing; Lee, Jin Woo; Hwang, Bang Yeon; Lee, Mi Kyeong
Graphical abstract A new benzylated and prenylated flavonoid, cudracuspiflavanone A, together with two chromones and fourteen flavonoids with pancreatic lipase inhibitory activity were isolated from the root barks of Cudrania tricuspidata.